PENGARUH PENDIDIKAN DAN PELATIHAN KEWIRAUSAHAAN TERHADAP MINAT USAHA JASA PARIWISATA DI KAMPUNG WASUR KABUPATEN MERAUKE - Luh Kadek Budi Kartini; Mutria Farhaeni; Katarina Mariana Yaas (Universitas Triatma Mulya, 2021)
The low entrepreneurial spirit of the community and the motivation of Indonesian’s young generation to be entrepreneurial and to create their own jobs have become serious thought in various parties, both the government, the world of education and the community. This research aimed to analyze the influence of Entrepreneurship Education and Training On the Interest In Tourism Service Businesses In Wasur Village Merauke Regency. The sample of this research is 50 active respondents as independent small business actor. The Data sources used in jrseruni@gmail.this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method, by means of questionnaires with likert scale. The analytical technique used is multiple linier regression analysis. Results of statistical analysis known that the entrepreneurship education and training influenced on the interest in tourism service businesses in Wasur Village Merauke Regency is 32%, based on hypothesis testing with the F and t test results, it can be concluded that the entrepreneurship education and training simultaneously (together and significantly influence on the interest in tourism service businesses with value of F-test is 11,063 and sig 0,000. The entrepreneurship education partially and significantly positive influenced on the interest in tourism service businesses with value of t-test is 3,242 and sig 0.002 and entrepreneurship training significantly positive influenced on the interest in tourism service businesses with value of t-test is 2,659 and sig 0,011 In Wasur Village Merauke Regency.